The role of tax exemption and financing and investment decisions on the performance of medical equipment companies - Abdolhamid Jahangirvand; Mohammad Reza Shurvarzi; Zahra Noori Tupkanloo (Shahid Beheshti University of Medical Sciences, 2023)
Background: This study aim was to investigate the relationship between the importance of tax exemption, financing and investment decisions on the performance of medical equipment companies in the capital market of Tehran. Methods: The research environment included Tehran capital market and the research population included 29 companies. Using random sampling method, 101 managers or financial and administrative deputies, financial managers, accounting heads and accounting experts were selected and questionnaires were distributed among them. Using SPSS22 software (demographic and reliability description) and Smart PLS2 software, confirmatory factor analysis (review of measurement model) and exploratory factor analysis (review of structural model), the fit and overall quality of the model was examined and research questions were analyzed. Results: Based on the results, tax exemption has a significant relationship with financing decisions of medical equipment companies in Tehran capital market. Tax exemption has a significant relationship with the investment decisions of medical equipment companies in the capital market of Tehran. Financing decisions have a significant relationship with the performance of medical equipment companies in Tehran's capital market. Also, investment decisions are significantly related to the performance of medical equipment companies in the Tehran capital market. Conclusion: It can be shown that the necessary support, such as tax exemption, will increase the performance of medical equipment companies in the Tehran capital market by influencing investment and financing decisions, considering the capacity of this sector and potential markets.